If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(j + -9) = 0 Reorder the terms: 9(-9 + j) = 0 (-9 * 9 + j * 9) = 0 (-81 + 9j) = 0 Solving -81 + 9j = 0 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + 9j = 0 + 81 Combine like terms: -81 + 81 = 0 0 + 9j = 0 + 81 9j = 0 + 81 Combine like terms: 0 + 81 = 81 9j = 81 Divide each side by '9'. j = 9 Simplifying j = 9
| lne^2x=8 | | f(x)=2x^2+14x+22 | | 6x-28=6x-4 | | 42-4u=3u | | x^2-6x-25/16 | | 6(2x-4)=8(x+2) | | 4(x-4)-1=-5(-5x+5)-7x | | (10x^3-18x^2)/2x^2 | | 3+2ab-4ac+6bc= | | 2(x-2)+2x=4 | | (X-19)+17=63 | | -24b=-48 | | 1p^2+2p-24=0 | | 7(b+10)= | | -2/3n-4=5 | | (x+16)(x-18)=180 | | 4x+10=3x-4 | | -2(u+1)=-2(9u-7)+4u | | 3(-2+7x)=-27 | | 1250w^10z^5/20w^2z^2 | | 2z+7=3z-11 | | 1-5x=6x-10 | | 3(u+2)+2u=7(u-1)+1 | | 3x+2(3x+5)-4(3x+4)+3(3x+2)+8=0 | | (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x |